Improving the performance of photocathodes in tandem dye-sensitised solar cells - Wood, C. J. (2017)
Tandem dye-sensitised solar cells, which contain two dye-sensitized electrodes (one p-type and one n-type), are often cited as a way of improving upon the standard devices, in which only the n-type electrode is photoactive. However, the p-type component of these devices suffers from very poor photocurrents, limiting the overall performance of the tandem cell. This Thesis aims to improve the performance of p-type dye-sensitised solar cells. An emphasis is made on tuning the energy levels of the different components of the device to ensure that the charge transfer processes which dictate the current and voltage are efficient. Chapters 1 & 2: A brief introduction to p-type and tandem dye-sensitised solar cells. The dye characterisation methods and techniques used to test complete devices are also discussed. Chapter 3: Dye synthesis and characterisation methods are presented as well as the apparatus used to characterise complete DSC devices. Material characterisation methods used in Chapter 6 are also discussed. Chapter 4: Novel dye structures were investigated for their use in p-type dye-sensitised solar cells. The optical and electrochemical properties of these dyes were investigated experimentally and by computational methods. It was found that the energies of the frontier orbitals of these dyes had a profound effect on charge transfer processes within p-DSCs. Charge recombination was investigated using small square wave modulated photovoltage and charge extraction measurements, this demonstrated that blocking units can be employed to inhibit this process. Transient absorption and time resolved infrared spectroscopies are employed to investigate the excited and charge separated state lifetimes of a number of these dyes. The dye CAD3 in this Chapter generated a record breaking photocurrent. This dye absorbed towards the red region (> 600 nm) of the visible spectrum, which made it ideal for use in tandem-DSCs in which red light is absorbed at the photocathode. Chapter 5: Three dyes, including CAD3 from Chapter 4 were used on the photocathode in tandem-DSCs. The photocurrent generated was largely dependent on the degree of spectral overlap between these dyes and the dye on the photoanode. CAD3, which absorbed at longer wavelengths than the other dyes, generated a record breaking photocurrent when paired with the literature n-type dye D35. However, these devices suffered from poor photovoltages as result of using an electrolyte solution optimised for p-DSCs. Chapter 6: Mg2+ doping studies were performed on the NiO films used in p-DSCs. It was found that higher concentrations of MgO improved the photovoltage of these devices. However, there was a notable drop in photocurrent with increasing Mg2+. From charge extraction experiments it was revealed that the cause of this was a positive shift in the energy of the valence band. This decreased the driving force for electron transfer from the NiO film to the dye and therefore the photocurrent. The MgO also had a profound effect on the morphology of the films. The larger pore volume in the 150-500 nm range lead to an improvement in dye adsorption, despite the overall surface area being slightly decreased. Chapter 7: Based on work by O’Regan et al., the effect of free iodine on p-DSCs was investigated. In this Chapter it was demonstrated that increased concentration of free iodine reduced the photovoltage obtained by a p-DSC. This was confirmed to be a result of increased charge recombination using small square wave modulated photovoltage and charge extraction measurements. The fact that increasing concentration of free iodine increased the rate of recombination so significantly indicates an alternate main pathway for recombination. This study was then repeated with increasing concentrations of triiodide, which was found to have little or no effect on the performance of the p-DSCs. Chapter 8: A concluding summary of the work presented in this Thesis. Future work is also discussed in this Chapter.